Polish Unit - Radio Free Europe/Radio Liberty Research Institute: Information Resources Department: East European Archives: Polish Unit
Materials in this subfonds include press clippings, news agency releases, Radio Free Europe/Radio Liberty research papers and background analyses, Information Items, index cards, posters, leaflets, telexes and letters. The records of the Polish Unit give a broad picture of postwar Polish political life, economics, culture and arts, religions, media, social, trade union and military issues. The files on the Solidarity movement give a wide picture about Poland in 1980-1985. Originating from unofficial and non-public but usually reliable sources (interviews with refugees, escapees, and dissidents), the Information Items also have a special value among the records, but unfortunately in 1973 the evaluators deleted most of the originals, and now these are researchable only in microfilm format. The biographical files, together with the biographic sections of the Subject Card Files, contain invaluable information on thousands of individuals playing major or less important roles in Poland's political, economic, and cultural life. The collected correspondence and telex materials are also valuable parts of the series. The Polish Unit has two very special and interesting series, which partly contain confidential documents even, on the Polish Secret Intelligence Service, and on different RFE operations. These are the Interviews with Jozef Swiatlo, Andrzej Czechowich, Mieczyslaw Lach and Andrzej Smolinski. The RFE News Bureaus' and the Confidential Reports also give a special and unic picture of Poland and the political movements in the 70's. Accruals not expected